Control Mechanism and Parameter Simulation of Oil-Water Properties on Spontaneous Imbibition Efficiency of Tight Sandstone Reservoir - Ren, Dazhong; Ma, Litao; Liu, Dengke; Tao, Jing; Liu, Xueqing; Zhang, Rongjun (Frontiers in Physics, 2022)
Spontaneous imbibition is an effective method of tight sandstone reservoirs development. However, their underlying mechanisms are still unclear due to the representative issue caused by strong heterogeneity and complex oil-brine properties. In this research, physical properties and thin-section images were systematically analyzed, and the spontaneous imbibition efficiency was examined from core tests. The results show that quartz and feldspar predominantly contribute to mineralogy. Low brine salinity, high oil viscosity, and high interfacial tension corresponded to strong spontaneous imbibition ability and fast process. High interfacial tension is the dominant controlling factor in this field. Furthermore, the parameter simulation model established by the dimension reduction method could catalyze the prediction of spontaneous imbibition efficiency, which is confirmed by higher reliability.